2020
DOI: 10.1002/agj2.20148
|View full text |Cite
|
Sign up to set email alerts
|

Integrated crop–livestock systems in paddy fields: New strategies for flooded rice nutrition

Abstract: Integrated crop-livestock systems (ICLSs) appear as a good alternative to increase nutrient use efficiency (NUE) in rice (Oryza sativa L.) through the improvement in nutrient cycling and soil chemical attributes in paddy fields. The objective of this study was to evaluate the impact of an ICLS on soil chemical attributes and on the fertilization requirement of N, P, and K by flooded rice in the Brazilian subtropical region. Nutritional status, yield, and NUE of flooded rice were evaluated by fertilization tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In addition, we have shown that not only nutrient cycling from one phase to another (pasture to crop) in the annual ICLS cycle is important, but also nutrient recycling in the pasture phase is a relevant process, both with potential to improve systems' nutrient-use efficiency. Recent studies [8,29] recommended that most of the P and K fertilizer should be applied prior to the grazing season in ICLS (i.e., at the beginning of the pasture phase) instead of the traditional fertilization in the crop phase. This change in the logic of fertilization management results in greater pasture yields and animal live weight gains (as a result of improved sward structures and stocking rates) with the same amount of nutrient input to the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have shown that not only nutrient cycling from one phase to another (pasture to crop) in the annual ICLS cycle is important, but also nutrient recycling in the pasture phase is a relevant process, both with potential to improve systems' nutrient-use efficiency. Recent studies [8,29] recommended that most of the P and K fertilizer should be applied prior to the grazing season in ICLS (i.e., at the beginning of the pasture phase) instead of the traditional fertilization in the crop phase. This change in the logic of fertilization management results in greater pasture yields and animal live weight gains (as a result of improved sward structures and stocking rates) with the same amount of nutrient input to the system.…”
Section: Discussionmentioning
confidence: 99%
“…Residue diversity also benefits soil microbial diversity, which is greater under moderate grazing intensities [7]. As a consequence, increased biodiversity has been recently acknowledged as the responsible for higher grain yields and nutrient use efficiencies under ICLS, ultimately reducing fertilizer requirements and increasing systems' self-sufficiency [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, during the 2015/2016 cropping season, soybean yield did not respond to P and K fertilization with average yield across treatments of ~4.5 Mg ha −1 (Figure 1). The lack of soybean yield response could be related to the greater cycling of P and K under an ICLS, favored by fertilized pasture residues and cattle manure [8,10]. The high pasture fertilization rates could have led to an accumulation of nutrients in the soil, contributing to a reduction in the response to mineral fertilizer in soybean.…”
Section: Soil Fertility Characterization and Soybean Yield Response Tmentioning
confidence: 99%
“…The benefits of legumes in rotation are not only caused by biological nitrogen (N) fixation but also by increased nutrient availability through higher microbial carbon use efficiency from legume residues that increase the soil organic matter content, which could help to sustain the long-term productivity of cereal-based cropping systems [6,7]. In addition, both rice and soybean benefit in this environment, which can be achieved under an integrated crop-livestock system (ICLS) [8,9]. These systems enhance the nutrient cycling process and increase both soil phosphorus (P) and potassium (K) supplies [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation